Assessing factors influencing adolescents' dietary behaviours in urban Ethiopia using participatory photography. Issue 12 (14th August 2021) - Trübswasser, Ursula; Baye, Kaleab; Holdsworth, Michelle; Loeffen, Megan; Feskens, Edith JM; Talsma, Elise F
Abstract: Objective: To assess factors influencing dietary behaviours of adolescents in Addis Ababa, Ethiopia. Design: Using the qualitative participatory method Photovoice, participants received training on the basics of Photovoice and took photographs related to (un)healthy eating in their environment. Transcripts of individual interviews, focus group discussions and photographs were coded for thematic analysis. Setting: One private and one public school located in the same, central neighbourhood in Addis Ababa, Ethiopia to explore how school populations of different socio-economic status experience the same neighbourhood environment. Participants: Twenty-six adolescents aged 14–19 years old, of which there were seventeen girls and nine boys. Results: Findings from the current study indicate that food safety concerns appear to be the major influencing factors for adolescents' dietary choices. Unhealthy and unsafe foods appear to be widely available and/or affordable in adolescents' neighbourhoods and almost half of the photographs taken by adolescents depicted poor hygiene conditions related to food vendors. Participants considered foods available in their environments as generally unsafe, calling for more packaged food. Conclusions: Concerns for food safety, hygiene and affordability are the dominating factors for adolescents' food choices. These concerns, together with limited nutrition knowledge and preference for packaged foods, could make cheap, ultra-processed packaged foods more desirable.